Understanding the Processes Leading to Ultrafine Particle Formation in Remote Environments - Myers, Deanna (eScholarship, University of California, 2022)
Atmospheric particles represent a large source of uncertainty in global radiative modeling, whichis driven largely by an incomplete understanding of the processes responsible for their formation and growth. Particles smaller than 100 nm in diameter, termed ultrafine particles, are of particular interest because of their potential to grow into cloud condensation nuclei (CCN). Their ability to act as CCN depends on numerous factors, including their chemical composition and physical properties. These properties depend on the conditions under which the particles formed, meaning that an improved understanding of these conditions will improve global climate modeling. There is currently a poor understanding of the processes leading to the formation and growth of these small particles in remote locations. This dissertation investigates the processes that lead to ultrafine particles in two remote environments: the Alaskan Arctic and the Amazon Basin.In Chapter 2, we reported indirect measurements of ultrafine particle composition made duringMarch 2009 in Utqiagvik, Alaska. We compare measurements of ambient size-selected ultrafine particles and those measured during two ultrafine particle growth events, all of which occurred during periods with minimal local emissions. The ambient particles were found to be moderately hygroscopic, with measured hygroscopic growth factors (HGFs) ranging from 1.45 to 1.51 at 90 % RH, and largely volatile. Combining these data, we estimated that the volume of these particles were comprised of oxidized organics (∼70 %) and ammoniated sulfates (∼30 %). The first ultrafine particle growth event was associated with both solar radiation and elevated levels of sulfuric acid at the site, and analysis of air mass back-trajectories indicated that this event was influenced by the upper marine boundary layer above the Arctic Ocean. The second event was not associated with solar radiation or sulfuric acid. Air masses for this event were close to the surface of the Arctic Ocean and passed over open ...